PCR optimization for isolation of resistance gene analogues (RGA) in Mustard Green (Brassica juncea) - Liyana Mohd Zuhar (2012)
Most of the disease resistance genes (R genes) in plants appear to encode nucleotide-binding site leucine-rich repeat (NBS-LRR) proteins characterized by nucleotide-binding site (NBS) and leucine-rich repeat (LRR) domains. The identification of resistance gene analogs holds great promise for development of resistant mustard green cultivars especially towards the traditional farming. Degenerate primers designed based on known resistance genes (R-genes) were used as PCR primers to isolate and amplify the resistance gene analogs in Brassica juncea. However, only Primer 2 had successfully amplified a major band of approximately 500 base pair under optimum PCR condition where the annealing temperature is 58°C with primer and magnesium concentration of 4 OA and 1.0 mM respectively. Moreover, Primer 2 has almost no degeneracy at the 3' end terminal for both its forward and reverse sequence. In contrast, Primer has several number of degeneracy at its 3' end terminal for both reverse and forward sequence. The primer that has the least degeneracy provides the greater specificity since degeneracy can lead to single based mismatch to occur thus obviate extension of desired DNA sequence. Therefore, this indicates that Primer 2 sequence has successfully anneal to kinase-la (P-loop) domain and the reverse primer to the hydrophobic (GLPL) domain in the resistance gene analogs from the DNA template in Brassica juncea.